2011
DOI: 10.4213/tvp4424
|View full text |Cite
|
Sign up to set email alerts
|

Уточнение Оценок Скорости Сходимости В Центральной Предельной Теореме При Отсутствии Моментов Порядков, Бо́льших Второго

Abstract: Уточнены верхние оценки абсолютной постоянной в оценке скорости сходимости в центральной предельной теореме в терминах урезанных моментов. Показано, что абсолютная константа в неравенстве Осипова не превосходит 2.011. Ключевые слова и фразы: центральная предельная теорема, оценка скорости сходимости, абсолютная константа.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Korolev and S. V. Popov [26] showed that there exist universal constants C 1 and C 2 which do not depend on a particular form of g ∈ G, such that inequalities (1), ( 2), ( 5) and ( 6) are valid with C 1 = C 4 3.0466 and C 2 = C ′ 3 3.1905. This result was later improved by the same authors in the papers [6,7], where it was shown that…”
Section: The History Of the Problem And Aims Of The Papermentioning
confidence: 80%
See 2 more Smart Citations
“…Korolev and S. V. Popov [26] showed that there exist universal constants C 1 and C 2 which do not depend on a particular form of g ∈ G, such that inequalities (1), ( 2), ( 5) and ( 6) are valid with C 1 = C 4 3.0466 and C 2 = C ′ 3 3.1905. This result was later improved by the same authors in the papers [6,7], where it was shown that…”
Section: The History Of the Problem And Aims Of The Papermentioning
confidence: 80%
“…In Section 3 the analogs of inequalities (1), ( 2), ( 3) and ( 6) are proved for Poisson-binomial and binomial random sums. In Section 4 the results obtained in Section 3 are used to construct the analogs of (1) and (6) for Poisson random sums. The results of Section 4 are used in Section 5 to obtain bounds for the accuracy of the approximation of the distributions of mixed Poisson random sums by the corresponding limit law.…”
Section: The History Of the Problem And Aims Of The Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Однако это нововведение не коснётся прочих приборов учёта -водоснабжение и водоотведение, а также газоснабжение. А для теплоснабжения внедрения телеметрии в рассматриваемом нами случае невозможно, дома имеют вертикальную разводку системы отопления и индивидуальный учёт в российских климатических условиях становится не целесообразен [6]. Расходы жильцов по оплате коммунальных ресурсов на общедомовые нужды могут быть ограничены даже при наличии общедомовых приборов учёта нормативным потреблением [7].…”
Section: повышение кризисной адаптации малых предприятий сферы жкх пу...unclassified
“…доказанной в 1963 г. М. Кацем [39] для одинаково распределенных слагаемых, и обобщенной позже на случай разнораспределенных слагаемых В. В. Петровым [21], где g(x) -четная функция, не убывающая вместе с x/g(x), A 2 -положительная конечная абсолютная постоянная. Недавно В. Ю. Королев и С. В. Попов [41] показали, что в общем случае необязательно одинаково распределенных слагаемых A 2 2.011, какой бы ни была функция g, удовлетворяющая указанным выше условиям.…”
Section: т е о р и я в е р о я т н о с т е йunclassified